Economic terminology and its difficulty of translation between Arabic and Spanish - Ali, Yasameen Karim; Nasser, Esam Ahmed (Al-Adab Journal, 2021)
The research focused on the difficulties that the translator faces when translates economic terms from Arabic and Spanish language and vice versa. The main objective of this research was finding effective solutions for these difficulties. The research concluded that There are some criteria that are essential for the success of the economic translation process that is of great importance in society today, among them: the understanding of the source text is considered as the cornerstone in the translation of specialized texts, therefore, Sometimes it takes more than one reading of the source text to reach an acceptable level of understanding, the need for the translator to have linguistic and cultural knowledge in both languages, the source and the target, the knowledge of the economic field , knowledge of translation techniques and research and documentation skills.